EFEFKTIFITAS PENERAPAN SISTEM MANAJEMEN DALAM MELAKSANAKAN KOORDINASI DAN PEMELIHARAAN SISTEM MANAJEMEN KESEHATAN DAN KESELAMATAN KERJA (SMK-3) PADA SUATU PERUSAHAAN (Universitas Muhammadiyah Palembang, 2023)
The method used in this article is a literature review, which is a review and discussion of literature in a particular research area, by peeling, comparing, summarizing and collecting literature and then drawing a conclusion. Implementation of SMK-3 requires commitment from companies as providers of vacancies. Management as directors and employees as resources that maintain the continuity of the company. The application often raises questions from both company management and employees. Companies are required to implement SMK-3 in the workplace by integrating the system with SMK-3. This obligation applies to companies with a workforce of at least 100 (one hundred) or less than 100 people, but which are classified as a high potential risk company. Iimplementing this Health and Safety Management System (SMK-3)it is hoped that it can increase workforce productivity.